Audit Kepastian Kualitas untuk Menilai Efektivitas Sistem Manajemen Mutu ISO 9001:2008 di UPT Perpustakaan Universitas Jember - Septarina Prita; Jean Suha Theresia Br. Aritonang; W. Wasito (UPT Penerbitan Universitas Jember, 2017)
Library is all about service, therefore UPT Perpustakaan Universitas Jember commited to always do a continuous improvement on their service by implying quality management systems ISO 9001:2008. Tools to evaluate the effectiveness of quality management systems is quality audit which is held by Badan Penjamin Mutu (BPM) and performed annually. Quality audit performed by interviewing respondents, ask the respondents to filling in the questionnaires, and the last method is observing the library activity, and analyzes if the reality meets the standards set by the UPT Perpustakaan itself. There are 3 types of finding resulted by quality audit avtivity, they are cathegorized as observative finding, minor finding and mayor finding. Minor findings have been found in Pembinaan Koleksi's sector and Gugus Penjamin Mutu's sector whilst the mayor findings coming from Sirkulasi's sector, Pengembangan dan Kerjasama's sector and Layanan Perujukan dan Koleksi Khusus's sector. Mayor findings means that management should give more attention to the implimentation of quality management system which is implied to these sectors because the findings can influence the conformity between the processes and the products offered so that those will affect the services's quality given by the library. Minor findings means that finding will not influences the quality of the services, and generally human error is the cause of that findings. But although it will not influences the quality of the services, the minor findings still needs to be documented and need a correction action to correct the findings so that in the future, the management can prevent similar findings to ever occured again.Keywords: ISO 9001:2008, Library, Quality Audit, Quality Management Systems